Hardware Implementation Of 2-D Discrete Wavelet Transform For JPEG 2000 Using Lifting Scheme - Bhuyan, Mohammad Shaharia (2008)
In this present research work, we have implemented a Lifting Scheme(LS) based 2-D DWT algorithm to achieve higher computational efficiency and less storage requirements for transformed image coefficients. The author focused on developing modular hardware architecture of the 2-D DWT suitable for Very Large Scale Integration (VLSI) implementations.